STRESS AND DEPRESSION AS CORRELATES OF RETIREMENT PHOBIA AMONG SECONDARY SCHOOL TEACHERS IN SOKOTO STATE, NIGERIA - Liman, B M; Abubakar, H S (Sokoto Educational Review, 2017)
The thrust of the study was to investigate stress and depression as correlates of retirement phobia among secondary school teachers in Sokoto state, Nigeria. The study employed descriptive research design, of correlational type. 260 respondents were selected using Krejcie and Morgan table from the total of 801 teachers from a total of 15 secondary schools in Sokoto state purposively selected. Three research instruments were used for data collection; Teachers Stress Scale, Perceived Teachers Depression Scale and Perceived Teachers Retirement Scale. Pearson Product Moment Correlation Coefficient was used for data analysis. The findings revealed that; there is significant relationship between stress and retirement phobia, depression and retirement phobia and stress and depression among secondary school teachers in Sokoto state. Recommendations forwarded includes Counselling Association should partner with Governments at all Levels to organizing programmes such as workshops, symposium and seminars; that are geared toward educating teachers on the danger of Stress and Depression on their retirement,